(untitled) (New York, 1997)
Something newly introduced; a new method or device; An improved management technique that escalates a business's success; The most effective and useful guide to making a business
Keywords: Đổi mới công nghệ,Technological innovations,Sản phẩm mới,New products; Quản trị,Management,Quản trị,Management; Hoa Kỳ,United States,Hoa Kỳ,United States